Unconscious response inhibition differences between table tennis athletes and non-athletes - You, Y.; Ma, Y.; Ji, Z.; Meng, F.; Li, A.; Zhang, C. (PeerJ, 2018)
Background: Response inhibition is associated with successful sporting performance. However, research on response inhibition in athletes from open-skill sports has mainly focused on a consciously triggered variety; little is known about open-skill athletes` response inhibition elicited by unconscious stimuli. Methods: Here, we explored unconscious response inhibition differences between table tennis athletes (n = 20) and non-athletes (n = 19) using the masked go/no-go task and event-related potentials technique (ERPs). Results: At the behavioral level, table tennis athletes displayed shorter go-response times (RTs) than non-athletes in the conscious condition. Furthermore, table tennis athletes exhibited longer response time-slowing (RT-slowing) than non-athletes in the unconscious condition. At the neural level, table tennis athletes displayed shorter event-related potential N2 component latencies than non-athletes for all conditions. More importantly, athletes displayed larger no-go event-related potential P3 component amplitudes than non-athletes at both the conscious and unconscious levels. Discussion: The present study results suggested that table tennis athletes have superior conscious and unconscious response inhibition compared to non-athletes.